Implementasi Strategi Membaca Berimbang di Kelas Awal Madrasah Ibtidaiyah (MI) di Semarang - Zulaikhah, Zulaikhah; Fadlilah, Sayyidatul (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2017)
This study aims at describing the implementation of impartial reading strategies namely collective reading, guided reading, and independent reading performed by teachers of early grades at Islamic Elementary School (MI and MIN) in six madrassas in Semarang. Implementation is conducted after the training of impartial reading is made and continued by providing assistance to teachers in creating impartial reading programs, applying impartial reading strategies, organizing the variety and types of books, and managing students in impartial reading. The program is focused on the use of books containing Islamic values as the development of modules or manuals that have been used to implement the strategy.